Hospital Medicine Perspectives, Practices and Professional Development - Habicht, Robert J.; Gulati, Mangla S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This practical resource provides hospitalists of all levels a comprehensive foundation for understanding the critical elements of hospital medicine. Beginning with an overview of the healthcare system, chapters provide relevant insights on management, regulations, evidence-based approaches, an awareness of safety and economic concerns and professional development skills. Perspectives on how hospitalist and hospital medicine teams can effectively engage this system to provide cost-effective, high-quality care are offered throughout this volume. With real-world guidance on the major tenets of hospital medicine, Hospital Medicine will serve as the definitive guide to a successful career in this rapidly evolving specialty.
Chapter 1 Primer on the Health Care System -- Chapter 2 Knowing Yourself and Your Style -- Chapter 3 Planning for a Career in Hospital Medicine -- Chapter 4 Common Career Pitfalls: Real-world guidance of common mistakes to avoid that may impact a hospitalist$1 (Bs ability to be successful -- Chapter 5 Goal-setting: Effective Strategies to Plan for a Successful Career -- Chapter 6 Work-Life Balance and Preventing Burnout -- Chapter 7 Women in Medicine -- Chapter 8 Basics of Billing and Coding: A Primer for the New Hospitalist Attending -- Chapter 9 Incorporating Evidence-Based Medicine into Your Daily Life -- Chapter 10 Interprofessional Collaboration -- Chapter 11 Transitions of Care -- Chapter 12 The Patient Experience -- Chapter 13 Consultative Medicine and Co-Management -- Chapter 14 Introduction to PSQI -- Chapter 15 Financial and Regulatory Drivers in Health Care -- Chapter 16 Demonstrating Value and Gaining Visibility: 13 Key Questions to Success -- Chapter 17 Cost-Conscious Care -- Chapter 18 Managing from the Middle -- Chapter 19 Teaching and Feedback -- Chapter 20 Engaging Others in Patient Safety and Quality Improvement -- Chapter 21 Introduction to Research as an Early Career Hospitalist.s
Keywords: Medicine; Health administration; Practice of medicine; Medicine & Public Health; Practice and Hospital Management; Health administration